The effect of Corporate Social Responsibility on corporate performance in Oil and Gas Industry - Alsamawi, Mohamed Abdulwali Ali; Mohd Ridzuan, Darun; Panigrahi, Shrikant; Al-Refaei, Abd Al-Aziz Hamed (Penerbit Akademia Baru, 2019)
This article investigates the causal impact of corporate social responsibility (CSR) on corporate performance. Although the social and political issues are the root cause of the threat to sustainability development in the world, only corporations have the three essential components, namely resources, global reach and motivation, in order to achieve sustainability. From the economic distress and social challenges that Yemen is facing, it is very important to understand the complex connection and interdependence of CSR activities. Data were collected by means of self administered survey questionnaire. A total of 339 usable responses were obtained from the employees working in three major oil and gas corporations in Yemen. The findings contribute to the literature of corporate communication to gain public legitimacy and corporate governance and develop a CSR model that explores critical dimensions in the management of corporate in Yemen Oil and Gas industry. The study result shows that CSR to employee dimensions play an important role in corporat performance. Corporate can achieve long term growth followed with maintaining effective CSR activities and achieve its reputation with an effective CSR strategies.